TECHNOLOGICAL PARTICULARITIES OF THE CIRCUIT BOARD WITH THE BUILT-IN INTERCONNECTION SYSTEM FORMATION FOR THE ANODE ALUMINA SUBSTRATE - G. V. Litvinovich; D. L. Shimanovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Results of the interconnection system formation during substrate anode alumina processing are presented. It is proved that anode Al2O3 substrate, interconnection system in the bulk and contact pads formation is possible simultaneously. The thickness of the anode Al2O3 substrate, the distribution of the interconnection system in its volume, the sizes of the conducting tracks and pads are specified by the method of the concrete board fabrication. It is possible to connect outboard or formed on the substrate surface later elements of integrated circuits with use external outputs with interconnection system.